Insight into norcantharidin, a small-molecule synthetic compound with potential multi-target anticancer activities - Mu-Su Pan; Jin Cao; Yue-Zu Fan (BMC, 2020)
Abstract Norcantharidin (NCTD) is a demethylated derivative of cantharidin, which is an anticancer active ingredient of traditional Chinese medicine, and is currently used clinically as a routine anti-cancer drug in China. Clarifying the anticancer effect and molecular mechanism of NCTD is critical for its clinical application. Here, we summarized the physiological, chemical, pharmacokinetic characteristics and clinical applications of NCTD. Besides, we mainly focus on its potential multi-target anticancer activities and underlying mechanisms, and discuss the problems existing in clinical application and scientific research of NCTD, so as to provide a potential anticancer therapeutic agent for human malignant tumors.